Authorship disputes: Do they result from inadvertent errors of judgment or intentional unethical misconduct? - Beshyah, Salem; Abdelmanna, Dima; Elzouki, Abdel-Naser; Elkhammas, Elmahdi (Ibnosina Journal of Medicine and Biomedical Sciences, 2018)
The frequency of conflicts about the authorship of publications has increased along with the increase in the number of people involved in scientific work and its complexity. Some of the factors that strongly influence the generation of conflicts and disputes in authorship definition are the pressure of competition in academia, economic incentives from the pharmaceutical industry in the field of biomedicine, and authors own wishes and expectations of recognition. It is necessary to have clear policies and apply more transparency to these activities. There are clear recommendations from the International Committee of Medical Journal Editors on authorships for medical articles. However, authorship disputes are still seen too often with a wide spectrum of reasons. These may reflect ignorance and errors of judgment on one end to intentional misconduct? In this article, we (1) revisit the international guidelines, (2) present and discuss illustrative examples of authorship disputes, and (3) explore possible solutions for authors and editors to avoid and resolve this problem. Solutions stem from the ethical imperative in clinical research, clear rules of engagement among research/authorship teams, and effective governance within research institutions.
Keywords: Authorship standards; authorship; collaboration; collegiality; conflict resolution; editorial; mentoring; multidisciplinary research teams; publication ethics; publishing; research ethics; research integrity; research misconduct; responsible publication